PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN STRATEGI PQ4R BAGI SISWA KELAS V SEKOLAH DASAR - Yanorita, Santi Prima (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The aim of this reseach is to improve reading comprehension of student of class  V at elementary school o3 Cingkariang city by using PQ4R. The arise problem of the reseach is the less understanding of student in reading comprehension. The object in this research are 30 students and teacher of elementary school number 03 Cingkariang Banuhampu. The aproach used in research are qualitative and quantitative. There are two cycles. The resuld of each cycles is carried out of this study saw an increase in reading comprehension. Kata Kunci : kemampuan, membaca pemahaman ,strategi PQ4R